Article Emergence in Old English a Constructionalist Perspective - Sommerer, Lotte (Topics in English linguistics ;, 2018)
This book investigates nominal determination in Old English and the emergence of the definite and the indefinite article. Analyzing Old English prose texts, it discusses the nature of linguistic categorization and argues that a usage-based, cognitive, constructionalist approach best explains when, how and why the article category developed. It is shown that the development of the OE demonstrative 'se' (that) and the OE numeral 'an' (one) should not be told as a story of two individual, grammaticalizing morphemes, but must be reconceptualized in constructional terms. The emergence of the morphological category 'article' follows from constructional changes in the linguistic networks of OE speakers and especially from 'grammatical constructionalization' (i.e. the emergence of a new, schematic, mostly procedural form-meaning pairing which previously did not exist in the constructicon). Next to other functional-cognitive reasons, the book especially highlights analogy and frequency effects as driving forces of linguistic change.